2016
DOI: 10.4028/www.scientific.net/msf.857.565
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Stress-Strain State of Multilayer Shell Molds

Abstract: The analysis of the trends for development of technological processes to form shell molds shows that the accuracy and purity of the surface of shaped castings are one of the main criteria for the level of development of the science and technology of foundry engineering. The equations of continuum mechanics and thermal conductivity and the numerical method were used to build a mathematical model of SSS of multilayer shell mold to determine the temperature fields in a shell mold and solidifying casting, thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Покажем, что система уравнений (4) -(6) эквива-лентна системе (1), (2). Выразим из уравнений (5) зна-чения σ ij = σδ ij + 2μξ ij и подставим их в уравнение дви-жения (4) …”
Section: для стационарного процессаunclassified
“…Покажем, что система уравнений (4) -(6) эквива-лентна системе (1), (2). Выразим из уравнений (5) зна-чения σ ij = σδ ij + 2μξ ij и подставим их в уравнение дви-жения (4) …”
Section: для стационарного процессаunclassified
“…Crack formation in SM is related to temperature impact arising during filling the molds with melt and thermoplastic stress state arising as result of no uniform heating as well as to low ceramic strength. Theoretical researches of these processes carried out by using numerical method are presented in works [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Porous layer created using the above-mentioned technology will act as a damper under the temperature impact. Research results of the stress-strain state of these SMs were presented in works [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress-strain state (SSS) of cylindrical shells is studied in papers [1,2], and papers [3,4] describe features of technology of electrophoretic process. Paper [5] uses the mathematical modeling to study SSS of multilayer shell molds. It is shown that during casting of metal, the greatest temperature differences occur between the first and second layers of the shell mold, and the maximum values of stresses and strains are typical for the first layer.…”
Section: Introductionmentioning
confidence: 99%